Tempeh Manufacturing Liquid Waste Treatment Using Alum Coagulant With Variation of Coagulant Weight - Winda Rohmah Shoffianti; Dila Argatiningtyas; Agus Aktawan; Imam Santosa; Mar’atul Husna (CHEMICA: Jurnal Teknik Kimia, 2023)
So far, liquid waste from the tempe industry has yet to be utilized and is only disposed of in sewers to the environment. The liquid waste from tempe consists of soluble proteins from soybeans, which can give rise to a sour smell, and there are tiny particles that settle, so it is necessary to treat the waste before it is discharged into the environment. Alum is one of the coagulants that can be used to treat liquid waste. This research contributes to determining the effect of alum as a coagulant in tempe industrial wastewater to obtain optimal results. The optimum results in question are an increase in DO levels and a decrease in COD and TSS levels in the tempe industrial wastewater so that the resulting conditions are not dangerous if the waste is disposed of into the environment. The variables observed in this study were pH, DO, COD, and TSS comparing each variable. The variable used in this study was the weight of the alum coagulant with a stirring speed of 300 rpm for 90 minutes and standing for 24 hours. In this study, there is a correlation of variations in coagulant weight. The optimum results obtained were from 100 ml of waste. The optimum DO value produced was 8.4 mg/L at an interpretation of 10 grams of coagulant weight. The optimum COD concentration obtained was 18612.5 mg/L at a variation of 20 grams of coagulant weight. The optimum TSS concentration obtained was 102 mg/L with 25 grams of coagulant weight variation.